2019
DOI: 10.1108/ijmpb-09-2018-0175
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of stakeholder engagement in mega transport infrastructure projects

Abstract: Purpose The purpose of this paper is to investigate the practice of stakeholder engagement as a social network dynamics for stakeholder satisfaction and project success in the lifecycle of mega transport infrastructure projects (MTIPs). Design/methodology/approach Hypotheses indicating the positive relationships between stakeholders’ effective attributes, stakeholder engagement as social network dynamics and project success through stakeholders’ satisfaction have been developed. Based on a questionnaire surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 122 publications
0
20
0
2
Order By: Relevance
“…In mega transport infrastructure projects, Erkul et al (2019) found a positive relationship between SE and project success through stakeholder satisfaction. SE activities included meetings, forums, workshops, negotiations, information hotlines, interviews, social contacts, public consultant approaches and surveys (Erkul et al , 2019). Project success was measured through capital performance, service provision, economic welfare and socio-environmental equity (Erkul et al , 2019).…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 95%
See 1 more Smart Citation
“…In mega transport infrastructure projects, Erkul et al (2019) found a positive relationship between SE and project success through stakeholder satisfaction. SE activities included meetings, forums, workshops, negotiations, information hotlines, interviews, social contacts, public consultant approaches and surveys (Erkul et al , 2019). Project success was measured through capital performance, service provision, economic welfare and socio-environmental equity (Erkul et al , 2019).…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 95%
“…However, in CPs, lack of communication among stakeholders has been identified as one of the main reasons for project failure (Bear, 2015). Although several studies have investigated the role and effects of engaging stakeholders in improving project success (Erkul et al , 2019), studies exploring the relationships between SE and both quantitative and qualitative PP in CPs have been limited. Moreover, Lehtinen et al (2019) called for more research into different contexts employing quantitative analyses to identify possible practices and rationales for SE.…”
Section: Introductionmentioning
confidence: 99%
“…The balancing feedback loop counteracts and controls the behaviour of a system (Kirkwood, 1998). By convention, stakeholder engagement proceeds in multiple process steps whereby one step of an action leads to another (Abuzeinab et al, 2014;Wid en et al, 2014) and sometimes in an iterative manner (Bal et al, 2013;Erkul et al, 2019). More recently, continuity in stakeholder engagement emerged in stakeholder management of mega construction projects as a continuous practice from the start to the end of project delivery (Butt et al, 2016;Yang et al, 2018).…”
Section: Progressing From the Rich Picture Diagram (Rpd) To The Causal Loop Diagram (Cld)mentioning
confidence: 99%
“…234), con lo que la relación de los administradores con los grupos de interés toma un carácter fiduciario (Freeman, 2007). En este sentido, los valores éticos son imprescindibles en los negocios (Freeman, Wicks, & Parmar, 2004) y deben guiar al gerente al plantear tanto los objetivos de la empresa como la clase de relaciones que le interesa y necesita generar con los grupos de interés para conseguir sus objetivos (Kreitner, 1983; Freeman, Wicks, & Parmar, 2004;Erkul, Yitmen, & Celik, 2019;Remme & de Waal, 2020).…”
Section: La Teoría De Los Stakeholders Y La éTicaunclassified
“…Lo que los autores Freeman, Wicks, y Parmar (2004) plantean que en la teoría de los stakeholders los valores éticos son esenciales para determinar la manera en que se deben realizar los negocios. Así, orientan a los gerentes a tener claros sus propósitos con el negocio y sus grupos de interés: en cuanto a qué tipo de relaciones necesitan desarrollar para cumplir su propósito (Kreitner, 1983;Freeman, Wicks, & Parmar, 2004;Erkul, Yitmen, & Celik, 2019;Remme & de Waal, 2020). Los planteamientos anteriores permiten entender que dicha teoría puede ser utilizada para establecer la relación entre la ética corporativa y los negocios, tal como lo expresó Freeman en (1994).…”
Section: La Teoría De Los Stakeholders Y La éTicaunclassified